PENINGKATAN KEAKTIFAN MURID DALAM PEMBELAJARAN IPAS MELALUI MODEL PjBL BERBANTU KUIS INTERAKTIF BERBASIS CANVA KELAS IV SD - Ayu Fitri Ani, Intan; Ninik Indawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of student participation in Grade IV Science and Social Studies (IPAS) at SDN Tanjungrejo 2 Malang. This condition was indicated by student’s passive behavior and lack of confidence during the learning process. The study aimed to improve student participation through the implementation of the Project-Based Learning (PjBL) model assisted by Canva-based interactive quizzes. The research employed Classroom Action Research using the Kemmis and McTaggart model, which consists of planning, acting, observing, and reflecting stages conducted in two cycles. The subject of this study were 28 fourth-grade students. Data were collected through observation, questionnaires, and documentation. The results showed a significant improvement in student participation, increasing from 50% in the first cycle to 85% in the second cycle, representing a 35% increase after the implementation of the PjBL model assisted by Canva-based interactive quizzes. The PjBL model provided meaningful learning experiences through project-based activities, while the interactive quizzes enhanced students’ interest, motivation, and confidence in expressing their ideas. Therefore, the implementation of the PjBL model assisted by Canva-based interactive quizzes proved to be effective in creating an active, interactive, and student-centered learning environment.